The Importance of Listening to Mud - Simon Connor; Rufus Maculuve (Kronos)
Mud is one of the most commonplace substances, but it defies attempts to describe it. Mud can be thought of as an archive in miniature, holding secrets about environmental change in deep time. This essay asks what we might be able to learn if we could listen to mud, to give voice to the history locked in its murky matrix. With examples from the arts and science, it explores mud as an environmental archive with the potential to provide rich, multisensory experiences of the past, particularly when transformed into soundscapes. By moving from scientific language to the immersive and empathic experience of soundscapes, knowledge can be shared more widely and everyone can play a part in interpreting environmental change.